Atividade e geração de valor no mercado imobiliário brasileiro e a arrecadação do ITBI na Cidade de Fortaleza - Muniz, Heloiza Beatriz da Silva (2020)
The study considers the importance of the real estate market to resume economic growth and evaluates in a national context its dynamics from indicators for the level of activity and for the generation of value arising from the sale of real estate between January 2014 and December 2019. Therefore, the analysis at the local level for the city of Fortaleza is specialized, with a third indicator obtained from the collection of the Tax on the Transmission of Property and Property (ITBI) in real terms. From descriptive statistics and econometric unit root tests on the developed indicators, there are indications of a resumption of the level of activity in the real estate market from January 2017, with the activity indicator suggesting a reduction in stocks of real estate units. Additionally, there is evidence of recovery also in value generation, but with a year of lag, since the trend of the sales value indicator shows signs of reversal only after January 2018. Finally, it is observed that these results have not yet shown robust in terms of the finding of an average reversal behavior, or an explosive dynamic of them. In local terms, it is verified that the ITBI of the city of Fortaleza presented a structural change from mid-2015, but with a reduction in average revenue around 50.0% from this date.